Pardes, Empat Tingkat Penafsiran Kitab Ibrani: Menimbang Sod Sebagai Penafsiran Esoterik Yang Mengundang Polemik - Yehuda Indra Gunawan; Abraham Pontius Sitinjak (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2021)
Pardes (sometimes written as 'PaRDeS') represents an abbreviation for: Peshat, Derash, Remez, and Sod apart from having different levels of search for meaning, but also unique in their way of interpretation. The advent of Pardes' hermeneutics has given direction to the world of Jewish hermeneutics. Pardes was the benchmark for hermeneutics in the Jewish tradition. Pardes becomes the standard in the steps of interpretation, mainly to examine the literary structure of the biblical text by considering the text as a whole based on their source language and combining relevant secondary and tertiary (third) background materials. Yet many theologians consider Sod, the highest level for interpreting the "hidden meaning", as an incomprehensible endeavor. The Sod approach in a unique way, namely esoteric interpretation, is regarded as something that cannot be revealed with certainty. Sod is doubtful about the level of accuracy in interpreting the biblical text. This article wants to review the extent of this hermeneutic interpretation polemic, and whether the esoteric approach of Sod in Pardes is still relevant for biblical hermeneutics today? This article will review it based on library research.AbstrakPardes (kadang ditulis ‘PaRDeS’) mewakili singkatan untuk: Peshat, Derash, Remez, dan Sod selain memiliki tingkatan yang berbeda dalam pencarian makna, tetapi juga memiliki keunikan tersendiri dalam cara menafsir. Hadirnya hermeneutik Pardes telah memberi arahan bagi dunia hermeneutik Yahudi. Pardes-lah yang menjadi tolok ukur hermeneutik dalam tradisi Yahudi. Pardes menjadi standar dalam langkah-langkah menafsir, utamanya untuk memeriksa struktur sastra dalam teks Kitab Suci dengan mempertimbangkan teks secara keseluruhan berdasarkan bahasa sumber mereka dan menggabungkan bahan latar belakang sekunder dan tersier (ketiga) yang relevan. Namun banyak teolog menganggap Sod, tingkatan tertinggi untuk menafsirkan “makna tersembunyi”, sebagai upaya yang tak mungkin dapat terselami. Pendekatan Sod dengan caranya yang khas yaitu penafsiran esoterik dianggap sebagai sesuatu yang tak mungkin dapat diungkap secara pasti. Sod diragukan tingkat keakuratannya dalam menafsir teks Kitab Suci. Artikel ini ingin mengulas sejauh mana polemik penafsiran hermeneutik ini, dan apakah pendekatan esoterik Sod dalam Pardes ini masih relevan bagi hermeneutik biblical di masa kini? Artikel ini akan mengulasnya berdasarkan riset kepustakaan.